The Effect of Servant Leadership and Organizational Commitment on the Performance of PLN ULP Wayhalim Employees - Arinaldo, Wendi; Efriyanti, Farida (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
The purpose of this study is to determine the Effect of servant leadership and organizational commitment on employee performance. Questionnaires were given to 44 respondents and analyzed using multiple linear regression, multiple correlation, ordination, F test and t test. Based on the calculation results of IBM SPSS Statistics Version 26, it was obtained that servant leadership had a positive and significant effect on the performance of PLN ULP Wayhalim employees. This means that the better the servant leadership applied, the better the work of PLN ULP Wayhalim employees. Organizational commitment has a positive and significant effect on the performance of PLN ULP Wayhalim employees. Organizational commitment has a positive and significant effect on the performance of PLN ULP Wayhalim employees. This means that the higher the commitment of employees to the organization, the better the work of PLN ULP Wayhalim employees. Servant leadership and organizational commitment have a positive and significant effect on the performance of PLN ULP Wayhalim This means that the better the servant leadership applied and the greater the commitment of the employee organization, the better the work of PLN ULP Wayhalim employees.